Comparing development and regeneration in the submandibular gland highlights distinct mechanisms. Issue 6 (16th January 2021) - Chatzeli, Lemonia; Teshima, Tathyane H. N.; Hajihosseini, Mohammad K.; Gaete, Marcia; Proctor, Gordon B.; Tucker, Abigail S.
Abstract: A common question in organ regeneration is the extent to which regeneration recapitulates embryonic development. To investigate this concept, we compared the expression of two highly interlinked and essential genes for salivary gland development, Sox9 and Fgf10, during submandibular gland development, homeostasis and regeneration. Salivary gland duct ligation/deligation model was used as a regenerative model. Fgf10 and Sox9 expression changed during regeneration compared to homeostasis, suggesting that these key developmental genes play important roles during regeneration, however, significantly both displayed different patterns of expression in the regenerating gland compared to the developing gland. Regenerating glands, which during homeostasis had very few weakly expressing Sox9‐positive cells in the striated/granular ducts, displayed elevated expression of Sox9 within these ducts. This pattern is in contrast to embryonic development, where Sox9 expression was absent in the proximally developing ducts. However, similar to the elevated expression at the distal tip of the epithelium in developing salivary glands, regenerating glands displayed elevated expression in a subpopulation of acinar cells, which during homeostasis expressed Sox9 at lower levels. A shift in expression of Fgf10 was observed from a widespread mesenchymal pattern during organogenesis to a more limited and predominantly epithelial pattern during homeostasis in the adult. This restricted expression in epithelial cells was maintained during regeneration, with no clear upregulation in the surrounding mesenchyme, as might be expected if regeneration recapitulated development. As both Fgf10 and Sox9 were upregulated in proximal ducts during regeneration, this suggests that the positive regulation of Sox9 by Fgf10, essential during development, is partially reawakened during regeneration using this model. Together these data suggest that developmentally important genes play a key role in salivary gland regeneration but do not precisely mimic the roles observed during development. Abstract : A common question in organ regeneration is the extent to which regeneration recapitulates embryonic development. To investigate this concept, we compared the expression of two highly interlinked and essential genes for salivary gland development, Sox9 and Fgf10, during submandibular gland development, homeostasis and regeneration. Our data suggest that developmentally important genes play a key role in salivary gland regeneration but do not precisely mimic the roles observed during development.